BASEL III, BANK FOR INTERNATIONAL SETTLEMENTS AND GLOBAL FINANCIAL GOVERNANCE - KHAN, Haider (Journal of Advanced Studies in Finance, 2013)
This paper analyzes the following aspects of global financial governance: proposed BASEL III reforms for more stringent capital requirements and their implications for the developing world in particular and Bank for International Settlements (BIS) proposals for better regulation of financial derivatives, including commodities futures, by moving away from OTC transactions towards organized exchanges. The Basel reforms and the BIS proposals for regulating the derivatives markets have many positive features. However, they have not been designed with the needs of DCs and LDCs in mind. The consequences of Basel I and II and proposed Basel III are analyzed from the perspective of the developing countries. It turns out that specific concerns of developing countries have not received adequate attention within the Basel Reform Initiatives and more can be and needs to be done.